Peran Diet Mediterania terhadap Kadar HbA1c pada Penderita Diabetes Mellitus Tipe 2 (Tinjauan Pustaka) - Arron Nathaniel Ginting; Reni Zuraida; Eka Putri Rahmadhani; Dian Isti Angraini (CV. Jasa Sukses Abadi, 2026)
Type 2 diabetes mellitus (DM) is a chronic metabolic disease and global health problem that requires optimal glycemic control to prevent complications. Medical nutrition therapy is a key pillar of management, with the Mediterranean diet recommended due to its nutrient profile rich in unsaturated fats. This review aims to synthesize the latest clinical evidence on the effect of the Mediterranean diet on reducing HbA1c levels in patients with type 2 DM, analyze the underlying biological mechanisms, and evaluate its sustainability compared to other diets. A literature review was conducted using the PubMed database for studies published between 2021 and 2025. Of the 60 articles, 6 clinical studies (RCTs, pilot studies, and prospective interventions) that met the inclusion criteria were analyzed. Data synthesis showed that Mediterranean diet interventions lasting 12 weeks to 12 months consistently reduced HbA1c levels with an absolute reduction range of 0.2% to 2.0% (p < 0.05). Critical interpretation shows that while restrictive diets such as the Ketogenic diet provide more drastic reductions (-9% to -13.5% relative) due to glucose elimination, the Mediterranean diet offers long-term metabolic stability through the restoration of insulin sensitivity. The mechanism of glycemic improvement occurs through anti-inflammatory pathways and modulation of the incretin system, particularly stimulation of the GLP-1 hormone. The Mediterranean diet has been shown to be effective in significantly lowering HbA1c and offers a more sustainable nutritional strategy for patients. Clinical implications suggest the integration of olive oil and plant-based diets as the standard for long-term nutritional therapy.